The genus Gertrudiella Broth. (Pottiaceae, Bryophyta) in Paraguay - Soledad Jimenez; Guillermo Suárez (Check List, 2017)
As part of a study of the bryophytes of South America, some samples collected in Paraguay were identified as Gertrudiella uncinicoma, a species of Pottiaceae characterized by the presence of a well-developed central strand and a thick-walled hyalodermis on the stem, lanceolate leaves, laminal cells ventrally mammillose, and several rows of guides cells at the transverse section of the costae. This work represents the first record of the genus from Paraguay. A complete description, ecological comments, illustrations in optical and scanning electron microscopy, and a distribution map are presented.